Prospective analysis of cerebrovascular events in patients following coronary artery bypass surgery - Kothamasu, Lakshmana Kumar Chaitanya Srinivasa; Sridhar, Louis Felix (International Surgery Journal, 2023)
Background: Cerebrovascular events are the most common cause of disability in adults and can be classified into two categories: ischemic stroke and hemorrhagic stroke. Risk factors for stroke include age, gender, race, family history of stroke, hypertension, smoking, heart disease, valvular heart disease, arrhythmias, diabetes, obesity, and dyslipidemia. Low cardiac output syndrome, myocardial infarction, and atrial fibrillation can also contribute to stroke. This study aims to investigate the incidence of stroke post-cardiac surgery and the risk factors contributing to it. Methods: A prospective observational study with a sample size of 516 patients was conducted. Patients over the age of 40 who were undergoing CABG (both off and on pump) were included. Patients were subjected to on-pump or off-pump coronary artery bypass surgery as per requirement, but preferably off-pump. Results: Out of 516 patients, 13 developed strokes, of which 8 (61.5%) had hypertension and 10 (76.9%) had diabetes, 4 (30.8%) were smokers, 6 (46.2%) had normal LDL values, 7 (53.8%) had high LDL levels, none had normal HDL values, 1 (7.7%) had normal LV function, 4 (30.8%) had mild LV dysfunction, 4 (30.8%) had moderate LV dysfunction, and 4 (30.8%) had severe LV dysfunction. 11 (84.6%) had COPD. 7 (53.8%) had no prior MI, 5 (38.5%) had a recent MI, and 1 (7.7%) had a prior MI that was more than ten years old. 8 (61.5%) had normal renal functions, while 5 (38.5%) had disturbed renal functions. Conclusions: In this study, the incidence of CVE after CABG is 2.52%. All the patients who developed stroke had multiple risk factors. High LDL, low LVEF, deranged renal functions, PVD, arrhythmia pre-op, anti-coagulation pre-op, on pump surgery, Cardioplegia usage, CCF pre-op, urgent surgery, LCOS post-operatively are risk factors for post-operative stroke.